PROMOTING ENGLISH SPEAKING THROUGH DAILY ENGLISH GAMBITS AMONG ISLAMIC ELEMENTARY SCHOOL STUDENTS - Raden Iyus Surya Drajat; Ahmad Masrul Anwar; Risa Rahmawati (Jurnal Intisabi, 2026)
Speaking skill in learning English as a foreign language (EFL) in primary school remain a challenge because students often have basic vocabulary but lack the courage and speech tools to participate orally. This study aims to analyze the shift in the function of daily English gambits from imitation and repetition to pragmatic use, and to identify differences in the adoption of routine expressions by student age. The research uses a qualitative approach with a longitudinal case study design during January-December 2025 at Madrasah Ibtidaiyah Andalan Ciamis. The research subjects were three students aged 12, 10, and 8 years old, purposively selected, with the classroom teacher as the supporting informant. Data were collected through participatory classroom observations and periodic semi-structured interviews, and were then analyzed thematically with attention to temporal development. The results showed that daily English gambits developed through a functional trajectory from imitation and directed participation to more independent pragmatic use. Older students tend to use gambits for clarification, turn management, and response drafting, while younger students use them as a means of basic participatory courage. This study concludes that daily English gambits are a simple yet strategic pedagogical tool for bridging students' linguistic limitations with their oral communication needs in elementary school EFL classes.